Association of intravenous heparin administration with in-hospital clinical outcomes among hospitalized patients with acute heart failure. (1st January 2023) - Hamatani, Yasuhiro; Kato, Takao; Morimoto, Takeshi; Iguchi, Moritake; Yaku, Hidenori; Inuzuka, Yasutaka; Kitai, Takeshi; Nagao, Kazuya; Tamaki, Yodo; Yamamoto, Erika; Ozasa, Neiko; Yamashita, Yugo; et al.
Abstract: Backgrounds: Patients with acute heart failure (AHF) possess a high risk for thromboembolism, and thromboembolism prophylaxis using heparin has been recommended by the guidelines. Methods: Among 4056 patients enrolled in the KCHF Registry, the current study population consisted of 2525 patients after excluding patients with acute coronary syndrome and oral anticoagulants on admission and those with mechanical circulatory supports. There were 789 patients (31%) with heparin administration within 24 h after admission, and 1736 patients (69%) without. Results: The baseline characteristics included mean age: 78 ± 13 years, New York Heart Association class IV: 51%, ischemic etiology: 30%, atrial fibrillation: 31% and mean left ventricular ejection fraction: 45%. During median hospitalization length of 16 days, 161 patients had all-cause death, 34 patients developed ischemic stroke, and 48 patients developed major bleeding. Multivariable logistic regression analyses demonstrated that heparin administration compared with no heparin administration was not associated with a lower risk for all-cause death (OR: 1.39, 95%CI: 0.90–2.15; P  = 0.14), nor for ischemic stroke (OR: 1.14, 95%CI: 0.53–2.43; P  = 0.74), but was associated with a higher risk for major bleeding (OR: 2.88, 95%CI: 1.54–5.41; P  < 0.001). Conclusions: In patients with AHF, heparin administration within 24 h after admission was not associated with a lower risk of all-cause death and ischemic stroke, but was associated with a higher risk of major bleeding during hospitalization. Our study raises questions about the routine use of heparin for thromboembolism prophylaxis in hospitalized patients with AHF. Further studies are warranted to address the utility of anticoagulant therapy in these patients. Highlights: Heparin was not associated with a lower risk of death and ischemic stroke in AHF. Heparin was associated with a higher risk of major bleeding in AHF. These results were consistent across major subgroups in AHF.